Assessing the Realization of Speech Acts in the Conversation Section of â€œInteractive English 1â€ Textbook - Millatuz Zulfa; Rahayu Puji Haryanti (English Education Journal, 2023)
Understanding speech acts and their functions is crucial for effective communication. Therefore, conducting research on the speech acts in English textbooks holds significant importance as it enables educators and curriculum designers to gain valuable insights into how language is used in real-life interactions. This study aimed to assess the speech acts realization in the English textbook entitled "Interactive English 1" for Seventh Grade of Junior High School. Qualitative study was employed for data collection, analysis, and drawing conclusions based on the findings of the analysis. The data were analyzed utterance by utterance by applying Searleâ€™s theory of speech act. This study analyzed 347 data (utterances) and found mostly stated in direct strategy with varying frequencies of speech act categories: assertive/representative (131 instances) as the most frequent with the functions of â€œinformingâ€, â€œintroducingâ€, â€œdescribingâ€, â€œstatingâ€, â€œconfirmingâ€, etc. Directive (107 instances) with the function of "inviting," "commanding," "requesting," and "advisingâ€ and â€œofferingâ€. Then, the speech act function of expressive (100 instances) observed in the conversations included "greeting", â€œparting", "stating pleasure", "thanking", etc. Followed by commisive (7 instances) with the function of â€œgrantingâ€, â€œpromisingâ€ and â€œofferingâ€. The least frequent was declaration (1 datum) in form of â€œdeclaringâ€. Based on the result, it is recommended that future English language teaching materials should emphasize pragmatic competence and provide adequate opportunities for learners to practice different speech act types to enhance their communicative abilities.